2022
DOI: 10.3389/fnins.2022.971144
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a 6-week controlled, hypocaloric ketogenic diet, with and without exogenous ketone salts, on cognitive performance and mood states in overweight and obese adults

Abstract: BackgroundKetogenic diets are a commonly used weight loss method, but little is known how variations in sodium content and ketones influence cognition and mood during the early keto-adaptation period.ObjectivesTo investigate the effects of an exogenous ketone salt (KS) as part of a hypocaloric KD on mood and cognitive outcomes in overweight and obese adults. A secondary objective was to evaluate changes in biochemical markers associated with inflammatory and cognitive responses.Materials and methodsAdults who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…In a 6 week controlled-KD intervention, no evidence of a constant decrease in mood or cognition performance was found in adults affected by overweight or obesity ( n = 13) aged between 21 and 65 years [ 62 ]. The insertion of a ketone salt into a well-formulated hypocaloric KD attenuated negative mood parameters during the early intervention stages with no evidential variations in cognitive function [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In a 6 week controlled-KD intervention, no evidence of a constant decrease in mood or cognition performance was found in adults affected by overweight or obesity ( n = 13) aged between 21 and 65 years [ 62 ]. The insertion of a ketone salt into a well-formulated hypocaloric KD attenuated negative mood parameters during the early intervention stages with no evidential variations in cognitive function [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a 6 week controlled-KD intervention, no evidence of a constant decrease in mood or cognition performance was found in adults affected by overweight or obesity ( n = 13) aged between 21 and 65 years [ 62 ]. The insertion of a ketone salt into a well-formulated hypocaloric KD attenuated negative mood parameters during the early intervention stages with no evidential variations in cognitive function [ 62 ]. A significant advantage of this survey was the presence of a controlled-nourishing design, which guarantees that participating individuals efficiently adopt the applied nutritional intervention [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cardona and coworkers [55] reported that eight weeks of multi-probiotic supplementation reduced errors of omission in Go trials (indicating an improvement in attention), with no impact on memory in patients with fibromyalgia. Moreover, Kackley and associates [56] reported that ingesting ketogenic salts may attenuate negative aspects of mood associated with diet intervention. Our group has also reported that acute and one-week ingestion of paraxanthine (the compound that caffeine is primarily converted into after ingestion) [33,57], as well as ashwagandha [58], appears to improve short-term memory, reaction times, and/or errors in healthy individuals.…”
Section: Discussionmentioning
confidence: 99%